Alienasi Pada Tokoh Utama Novel Ningen Shikkaku Karya Dazai Osamu - Aenum, Nur; Anwar, Fithyani (HUMANIKA, 2024)
The novel is one of the most popular forms of literature that serves as a medium for authors to represent their characters. Novels are literary works that can represent the life of society and a means of criticizing the social phenomena witnessed by the author. One of the novels that illustrates the social phenomenon of alienation in Japanese society is Ningen Shikkaku by Dazai Osamu. This study uses a descriptive qualitative approach to analyze social phenomena in Ningen Shikkaku to identify the phenomenon of alienation using Melvin Seeman's theory of alienation, which is grouped into five aspects, including powerlessness, meaninglessness, normlessness, social isolation, and self-estrangement experienced by the main character Yozo Oba. The results show that the five aspects of alienation experienced by Yozo gradually became primarily relevant to what happened in Japanese society at that time. His father controls Yozo's life, and he does not know what he wants and does not want, so he lives a life without meaning and purpose. Yozo is also dominated by feelings of emptiness or loss of meaning, which leads to a desire to end his life. Yozo also experiences social isolation and alienation. In Japanese society, suicide or hikikomori as an effect of alienation, like Yozo's, is common until now.